Pengaruh Pendapatan dan Motivasi Kerja Terhadap Kinerja Bidan di UPF Kebidanan Rumah Sakit Umum Prof. Dr. H. Aloei Saboe - Adam, Wirdawaty (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2015)
Health workers are professionals, have characteristics such as developing a unique service to the community, education program, have scientific knowledge, professional duties according to the code of ethics, are free to make decisions in running the profession, received a fee for the services provided, have a professional organization that is constantly improving the quality of service provided to the community. An important aspect to note is the indicator of performance factors midwives in implementing MCH services are influenced by several factors such indicators midwives work motivation and awards received for all the efforts that have been made .. Based on the above it, then the writer interested in studying these problems with title: